Effect of Process Parameters on Short Fiber Orientation along the Melt Flow Direction in Water-Assisted Injection Molded Part - Haiying Zhou; Hesheng Liu; Qingsong Jiang; Tangqing Kuang; Zhixin Chen; Weiping Li (Advances in Materials Science and Engineering)
The short fiber orientation (SFO) distribution in the water-assisted injection molding (WAIM) is more complicated than that in traditional injection molding due to the new process parameters. In this work, an improved fiber orientation tensor method was used to simulate the SFO in WAIM. The result was compared with the scanning electron micrograph, which was consistent with the experiments. The effect of six process parameters, including filling time, melt temperature, mold temperature, delay time, water pressure, and water temperature, on the SFO along the melt flow direction were studied through orthogonal experimental design, range analysis, and variance analysis. An artificial neural network was used to establish the nonlinear agent model between the process parameters and A11 representing the fiber orientation in melt flow direction. Results show that water pressure, melt temperature, and water temperature have significant effects on SFO. The three-dimensional (3D) response surfaces and contour plots show that the values of A11 decrease with the increase in water pressure and melt temperature and increase as the water temperature rises.